Second Five Year Plan Detailed Budget Estimates of Plan Schemes 1958-59 Government of Kerala - Planning Commission (Planning Commission, 1958)
Up to the end of the first year of the Second Five Year Plan, the expenditure on ‘ Plan ’ Schemes used to be booked in the State Accounts under a distinct minor head, “DEVELOPMENT SCHEMES” opened under the relevant major heads of account- This system of separate classification of Plan Expenditure was afterwards abandoned on the advice of the Comptroller and Auditor General of India. The resultant merger of Plan and Non-Plan expenditure, however, created difficulties in the matter of assessing the progress of expenditure on Plan Schemes and ^accordingly after reviewing the position, the Comptroller and Auditor-General again advised that with effect from the accounts for 1958-59, the expenditure of each Department should be recorded in two columns.
Government of Kerala